Epidemiological survey of dengue, chikungunya and Zika virus cases in northwest macro region of Paraná state in 2015 to 2020 period (Research, Society and Development, 2020)
Aedes aegypti transmits arboviral diseases of importance to public health, including those caused by the zika virus, dengue, chikungunya and yellow fever. The rapid and continuous emergence of viruses transmitted by arthropods (arboviruses) represents a serious challenge to public health. Several factors, such as urbanization, increased travel and climate change, are fueling local outbreaks and global spread. Objective: this study consisted of an epidemiological survey of dengue, chikungunya and Zika virus cases in the northwest macro-region of Paraná state.  Methodology: a survey of dengue, chikungunya and zika virus cases recorded from 2015 to 2020 in northwest  macro-region of Paraná state was carried out. The methodology used was based on the notifications in the form of weekly bulletins provided by the Health Department of Paraná state presented in the form of epidemiological weeks. Results: it was found indicated that the cases/ mortality from dengue were the most expressive, when compared to the cases/ mortality from chikungunya and zika virus in the analyzed period. Another point that draws attention was that the increase or decrease in cases mortality among the three diseases did not occur proportionally, and this finding can be evidenced in the week of number 36 more cases of zika virus (93 cases); and week number 43 with 97288 cases and 78 dengue deaths, against 2 cases of chikungunya and 1 case of Zika virus. Conclusion: to date, there is no method available to eradicate this culicid, with the need to raise public awareness in order to contain the spread of A. aegypti, avoiding the spread of pathologies arising from its bites.